POSSIBLE ROLE OF EXERCISE IN AGING - Beti Dejanova; Suncica Petrovska; Lidija Todorovska; Sanja Mancevska; Jasmina Pluncevic Gligoroska; Petar Dejanov (Faculty of Physical Education, Sport and Health in Skopje, 2016)
It is known that well balanced exercise slows down the aging process. The aim of the study was to determine the influence of exercise on endothelial stability related to the anti-aging process. Male healthy subjects (n=58) were submitted to the study: I – physically active subjects (n=21); II – previous physically active subjects (n=14) and III – sedentary subjects (n=23). Endothelial function was examined by following methods: nitric oxide - NO (Oxis, USA); free radicals - FR (Diacron, Italy); and superoxide dismutase in plasma and in red blood cells - SOD (Randox, G. Britain). Statistical significance for increased NO was found in I and II group compared to III group (p<0.01). FR was found decreased in I group (p<0.05) compared to other two groups. Plasma SOD was found decreased in III group (p<0.05). Exercise may increase NO production due to the muscles oxygen demand and may slow down the aging process.
Keywords: aging; exercise; endothelial function